Tissue Processor Based PLC (Programmable Logic Controller) - Ferdianita Neny; Her Gumiwang Ariswati; Tri Bowo Indrato (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2019)
Tissue Processor Tissue Processor consists of consists of several stages of dehydration, clearing, and paraffin infiltration.Phase dehydration to remove water content in tissues by immersion into alcohol. Clearing stage is the process of pulling out the alcohol content in the network by using a liquid xylol. Paraffin infiltration stages is the stage of filling cavities with liquid paraffin tissue. The purpose of this research is to modify the equipment that had broken before became an useful equipment that use basic controlled PLC. This modification tool-making using the "one-group posttest design" by treatment of the instrument without first measuring the initial state, the results of treatment directly measured without comparison to a control group. Making the modification tool using PLC as the main controller throughout the series. The tool mechanical motion using DC motors and AC motors as well as the use of two sensors limit switch as the controller limits the motor movement. Based on the results obtained temperature measurement error with the largest value of 4.44% in paraffin heater tube 1 and the biggest error of 4.0% in paraffin heater tube 2. While the measurement time of each - each tube obtained the smallest error on the tube-to-one by 0 , 03%, and the biggest error of measurement contained in the tube to the fourth, fifth, sixth, eighth and tenth of 0.16%.